Screening Mycelium of Macrofungi Isolates in Tahura Djuanda Bandung As A New Candidate for Biomaterial - Inneke Andita Putri Laoli; Asri Peni Wulandari; Ulyaa Rachmawati; Dwi Ramadhani Sukmana; Annisa Handayani Dewi; Nia Rossiana (Jurnal Biodjati, 2024)
Abstract. Cardamom (Amomum compactum) is an aromatic spice plant with numerous benefits, widely used in cooking, medicine, and beverages. The high demand for cardamom remains unmet due to the lengthy germination period required for cardamom seeds and the inability of cardamom shoots to thrive when planted independently from the mother plant. The presence of the mother plant significantly impacts cardamom nurseries utilizing shoots, making it challenging to obtain large quantities of nursery transplants. Growth stimulants, such as vitamin B1 and Indole Butyric Acid (IBA), are required to enhance vegetative growth in plants. Vitamin B1 (IPI brand) is applied due to its ease of accessibility and cost-effectiveness. Meanwhile, IBA is utilized for its accessibility, stable chemical content, and prolonged efficacy. This research aims to determine the optimal concentration of vitamin B1, IBA, and their combination to enhance the growth of mother and tiller shoots of cardamom ex vitro. The research employed a two-factorial Randomized Complete Block Design, with vitamin B1 concentrations of 21.5% and 43% and IBA concentrations of 0.75 ppm and 150 ppm. The treatment V1I1 (vitamin B1 21.5% and IBA 75 ppm) on mother plant shoots maintained a survival rate of 67% up to 12 Weeks After Planting (WAP). The interaction between vitamins B1 and IBA exhibited no significant effect on all parameters of mother shoots and tillers; however, vitamin B1 significantly influenced the vegetative growth of cardamom mother shoots. Vitamin B1 at 43% produced a significantly higher number of leaves compared to 21.5%. Thus, vitamin B1 at 43% is recommended for cardamom propagation, while vitamin B1 at 21.5% has the potential to enhance the average growth of tiller shoots across all parameters. HTML Source code: Abstract. Cardamom (Amomum compactum) is an aromatic spice plant with numerous benefits, widely used in cooking, medicine, and beverages. The high demand for cardamom remains unmet due to the lengthy germination period required for cardamom seeds and the inability of cardamom shoots to thrive when planted independently from the mother plant. The presence of the mother plant significantly impacts cardamom nurseries utilizing shoots, making it challenging to obtain large quantities of nursery transplants. Growth stimulants, such as vitamin B1 and Indole Butyric Acid (IBA), are required to enhance vegetative growth in plants. Vitamin B1 (IPI brand) is applied due to its ease of accessibility and cost-effectiveness. Meanwhile, IBA is utilized for its accessibility, stable chemical content, and prolonged efficacy. This research aims to determine the optimal concentration of vitamin B1, IBA, and their combination to enhance the growth of mother and tiller shoots of cardamom ex vitro. The research employed a two-factorial Randomized Complete Block Design, with vitamin B1 concentrations of 21.5% and 43% and IBA concentrations of 0.75 ppm and 150 ppm. The treatment V1I1 (vitamin B1 21.5% and IBA 75 ppm) on mother plant shoots maintained a survival rate of 67% up to 12 Weeks After Planting (WAP). The interaction between vitamins B1 and IBA exhibited no significant effect on all parameters of mother shoots and tillers; however, vitamin B1 significantly influenced the vegetative growth of cardamom mother shoots. Vitamin B1 at 43% produced a significantly higher number of leaves compared to 21.5%. Thus, vitamin B1 at 43% is recommended for cardamom propagation, while vitamin B1 at 21.5% has the potential to enhance the average growth of tiller shoots across all parameters. Chat GPT: Abstract. Cardamom (Amomum compactum) is an aromatic spice plant with numerous benefits, widely used in cooking, medicine, and beverages. The high demand for cardamom remains unmet due to the lengthy germination period required for cardamom seeds and the inability of cardamom shoots to thrive when planted independently from the mother plant. The presence of the mother plant significantly impacts cardamom nurseries utilizing shoots, making it challenging to obtain large quantities of nursery transplants. Growth stimulants, such as vitamin B1 and Indole Butyric Acid (IBA), are required to enhance vegetative growth in plants. Vitamin B1 (IPI brand) is applied due to its ease of accessibility and cost-effectiveness. Meanwhile, IBA is utilized for its accessibility, stable chemical content, and prolonged efficacy. This research aims to determine the optimal concentration of vitamin B1, IBA, and their combination to enhance the growth of mother and tiller shoots of cardamom ex vitro. The research employed a two-factorial Randomized Complete Block Design, with vitamin B1 concentrations of 21.5% and 43% and IBA concentrations of 0.75 ppm and 150 ppm. The treatment V1I1 (vitamin B1 21.5% and IBA 75 ppm) on mother plant shoots maintained a survival rate of 67% up to 12 Weeks After Planting (WAP). The interaction between vitamins B1 and IBA exhibited no significant effect on all parameters of mother shoots and tillers; however, vitamin B1 significantly influenced the vegetative growth of cardamom mother shoots. Vitamin B1 at 43% produced a significantly higher number of leaves compared to 21.5%. Thus, vitamin B1 at 43% is recommended for cardamom propagation, while vitamin B1 at 21.5% has the potential to enhance the average growth of tiller shoots across all parameters. Abstract. Cardamom (Amomum compactum) is an aromatic spice plant with numerous benefits, widely used in cooking, medicine, and beverages. The high demand for cardamom remains unmet due to the lengthy germination period required for cardamom seeds and the inability of cardamom shoots to thrive when planted independently from the mother plant. The presence of the mother plant significantly impacts cardamom nurseries utilizing shoots, making it challenging to obtain large quantities of nursery transplants. Growth stimulants, such as vitamin B1 and Indole Butyric Acid (IBA), are required to enhance vegetative growth in plants. Vitamin B1 (IPI brand) is applied due to its ease of accessibility and cost-effectiveness. Meanwhile, IBA is utilized for its accessibility, stable chemical content, and prolonged efficacy. This research aims to determine the optimal concentration of vitamin B1, IBA, and their combination to enhance the growth of mother and tiller shoots of cardamom ex vitro. The research employed a two-factorial Randomized Complete Block Design, with vitamin B1 concentrations of 21.5% and 43% and IBA concentrations of 0.75 ppm and 150 ppm. The treatment V1I1 (vitamin B1 21.5% and IBA 75 ppm) on mother plant shoots maintained a survival rate of 67% up to 12 Weeks After Planting (WAP). The interaction between vitamins B1 and IBA exhibited no significant effect on all parameters of mother shoots and tillers; however, vitamin B1 significantly influenced the vegetative growth of cardamom mother shoots. Vitamin B1 at 43% produced a significantly higher number of leaves compared to 21.5%. Thus, vitamin B1 at 43% is recommended for cardamom propagation, while vitamin B1 at 21.5% has the potential to enhance the average growth of tiller shoots across all parameters. <!DOCTYPE html> Abstract Abstract. Cardamom (Amomum compactum) is an aromatic spice plant with numerous benefits, widely used in cooking, medicine, and beverages. The high demand for cardamom remains unmet due to the lengthy germination period required for cardamom seeds and the inability of cardamom shoots to thrive when planted independently from the mother plant. The presence of the mother plant significantly impacts cardamom nurseries utilizing shoots, making it challenging to obtain large quantities of nursery transplants. Growth stimulants, such as vitamin B1 and Indole Butyric Acid (IBA), are required to enhance vegetative growth in plants. Vitamin B1 (IPI brand) is applied due to its ease of accessibility and cost-effectiveness. Meanwhile, IBA is utilized for its accessibility, stable chemical content, and prolonged efficacy. This research aims to determine the optimal concentration of vitamin B1, IBA, and their combination to enhance the growth of mother and tiller shoots of cardamom ex vitro. The research employed a two-factorial Randomized Complete Block Design, with vitamin B1 concentrations of 21.5% and 43% and IBA concentrations of 0.75 ppm and 150 ppm. The treatment V1I1 (vitamin B1 21.5% and IBA 75 ppm) on mother plant shoots maintained a survival rate of 67% up to 12 Weeks After Planting (WAP). The interaction between vitamins B1 and IBA exhibited no significant effect on all parameters of mother shoots and tillers; however, vitamin B1 significantly influenced the vegetative growth of cardamom mother shoots. Vitamin B1 at 43% produced a significantly higher number of leaves compared to 21.5%. Thus, vitamin B1 at 43% is recommended for cardamom propagation, while vitamin B1 at 21.5% has the potential to enhance the average growth of tiller shoots across all parameters. Abstract. Cardamom (Amomum compactum) is an aromatic spice plant with numerous benefits, widely used in cooking, medicine, and beverages. The high demand for cardamom remains unmet due to the lengthy germination period required for cardamom seeds and the inability of cardamom shoots to thrive when planted independently from the mother plant. The presence of the mother plant significantly impacts cardamom nurseries utilizing shoots, making it challenging to obtain large quantities of nursery transplants. Growth stimulants, such as vitamin B1 and Indole Butyric Acid (IBA), are required to enhance vegetative growth in plants. Vitamin B1 (IPI brand) is applied due to its ease of accessibility and cost-effectiveness. Meanwhile, IBA is utilized for its accessibility, stable chemical content, and prolonged efficacy. This research aims to determine the optimal concentration of vitamin B1, IBA, and their combination to enhance the growth of mother and tiller shoots of cardamom ex vitro. The research employed a two-factorial Randomized Complete Block Design, with vitamin B1 concentrations of 21.5% and 43% and IBA concentrations of 0.75 ppm and 150 ppm. The treatment V1I1 (vitamin B1 21.5% and IBA 75 ppm) on mother plant shoots maintained a survival rate of 67% up to 12 Weeks After Planting (WAP). The interaction between vitamins B1 and IBA exhibited no significant effect on all parameters of mother shoots and tillers; however, vitamin B1 significantly influenced the vegetative growth of cardamom mother shoots. Vitamin B1 at 43% produced a significantly higher number of leaves compared to 21.5%. Thus, vitamin B1 at 43% is recommended for cardamom propagation, while vitamin B1 at 21.5% has the potential to enhance the average growth of tiller shoots across all parameters. Abstract. Type 2 diabetes mellitus (DM) is a chronic metabolic disorder characterized by elevated blood glucose levels due to insulin resistance. Type 2 diabetes is considerably more prevalent than other forms (85–90%). The risk of type 2 diabetes is higher in women (53.2%). There is an urgent requirement for better and more affordable treatment options considering DM therapy is expensive and may have adverse health effects. The study's objective is to examine how acute toxicity, blood glucose levels, and body weight are affected by Moringa leaf ethanol extract (MLEE). Maceration was employed to eliminate the leaves of the moringa plant. Phytochemical screening was completed to assess the total flavonoid content and screen for alkaloids, flavonoids, phenolics, saponins, and tannins. Acute toxicity testing was performed following OECD guideline 423. Clinical symptoms of acute toxicity were observed every 30 minutes for the first 24 hours post-treatment, followed by observations every 24 hours up to 14 days. The estimated LD50 range was determined. Streptozotocin/ nicotinamide-induced female Mus musculus was administered to evaluate the antidiabetic potential of MLEE. Six groups of mice were utilized, which included a healthy control group (aquades not induced), a negative control group (induced aquades), a positive control group (induced glimepiride 0.8 mg/kg BW), and three treatment groups with varying dosages of MLEE (induced; 0, 100, and 150 mg/kg BW). A semi-auto chemical analyzer was employed on days 0 through 31 to determine blood glucose levels. An analytical digital balance was utilized to calculate the body weight. With a total flavonoid concentration of 20.75%, MLEE incorporated alkaloids, flavonoids, phenolics, saponins, and tannins. MLEE demonstrated a significant effect in lowering blood glucose levels at a dose of 100 mg/kg BW (P<0.05). A significant positive correlation has been identified between body weight and blood glucose levels (P<0.05). Soil arthropods play an important role in nutrient cycling and maintenance of soil structure. Thus, their abundance and diversity can indicate the biological quality of the soil. Due to different soil management practices, arthropods are also very sensitive to environmental changes. This study aims to analyze the abundance and diversity of soil arthropods and the environmental factors that support the abundance of soil arthropods in terrestrial of Situ Lengkong Panjalu, West Java, Indonesia. The methods used to obtain samples of soil arthropods are pitfall trap. Soil arthropod data were analyzed to determine the Shannon diversity index (H'), Margalef richness index (R), and Evenness index (E). The effect of abiotic environmental factors was analyzed using Principal Component Analysis (PCA). A total of 1263 arthropods were found in Situ Lengkong Panjalu, belonging to 11 orders, 24 families, and 32 morphospecies. The current work determined the scores of H'= 2.08, R = 3,08, and E = 0.72 of soil arthropods in Situ Lengkong Panjalu, West Java, Indonesia. Results revealed that humidity is one such environmental parameter affecting the presence of soil arthropods in Situ Lengkong Panjalu, West Java, Indonesia. This research can be used as a guide in validating and conservation of the habitat of soil arthropod species on West Java Obesity has a 15-fold higher risk of coronary heart disease, stroke, and diabetes mellitus. Microalga isone of the natural resources that potentially treat obesity. The purpose of this study was to evaluate the total phenolic contents (TPC), antioxidant, and anti-obesity properties of ethanolic extract of microalgae strain MRB-2. The TPC was determined using the Follin-Ciocalteu method. The antioxidant activity was evaluated using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) method, and the anti-obesity was analyzed using an anti-lipase pancreatic assay. The morphology of microalga cells was also determined using Scanning Electron Microscopy (SEM). The results revealed that the TPC of ethanolic extract from the ultrasound extraction method was higher than the maceration method with the value of 2.75±0.26 mg GAE/g. While the scavenging activity toward DPPH radicals of ethanolic extract from the maceration method was higher than ultrasound, with a value of 38.92±1.94% at 0.8 mg/mL. The lipase inhibitory activity of extract from the maceration method was higher than ultrasound with a value of 20.81±2.24% at 0.38 mg/mL. Our results indicate that ethanolic extract of MRB-2 was potentially developed for anti-obesity foods and health-functional foods derived from new peatland microalgae. Talinum paniculatum Jacq (Gaertn), locally known as Javanese Ginseng, is an essential medicinal plant characterized by high flavonoid content with antioxidant and antimicrobial activities. Compared to other natural sources, a larger number of T. paniculatum leaves is required to obtain high amounts of flavonoid for drug development. In this context, in vitro culture can be used to increase flavonoid production in a controlled condition without reducing plant population. The concentration of Plant Growth Regulators (PGRs) is capable of influencing biomass and flavonoid accumulation in callus culture from several species. Despite these benefits, there is limited information about the optimal concentration of PGRs for flavonoid production from T. paniculatum callus culture. Therefore, this study aimed to investigate the optimum concentration of 2,4-D and kinetin for callus growth, as well as flavonoid production from T. paniculatum. The investigation was carried out using a completely randomized design (CRD), where young leaves explants were cultured on MS media supplemented with various concentrations of 2,4-D (0, 0.5, 1, 2) mg/L and kinetin (0, 0.5, 1, 2) mg/L for callus and flavonoid production. The results showed that the highest callus biomass of 0.105 g was produced from MS medium with 2 mg/L of 2,4-D and 1 mg/L of kinetin. Meanwhile, the highest total flavonoid content of 25.66 mg QE/g DW was produced from media supplemented with 1 mg/Lof 2,4-D and 2 mg/L of kinetin. These results showed that different combinations of 2,4-D and kinetin were required to increase biomass and flavonoid production. In conclusion, this study provided valuable information for the development of bioactive compounds through in vitro culture. The mistletoe (Scurrula ferruginea) is a parasitic plant obtaining nutrients and water from host plants at Nglinggo tea plantation, Kulon Progo, Yogyakarta. Despite the numerous benefits of Scurrula ferruginea leaf, substantiation regarding its pharmacological activity is still lacking. Therefore, this research aimed to identify Scurrula ferruginea species and obtain secondary metabolites with antibacterial activity. The experiment was carried out by extracting Scurrula ferruginea leaf using maceration methods with 96% ethanol, followed by qualitatively and quantitatively phytochemical screening, inhibitory zone test, minimum inhibitory concentration (MIC), and minimum bactericidal concentration (MBC) test. Several compounds, such as flavonoids, tannins, phenols, saponins, alkaloids, terpenoids, and steroids, were identified in the mistletoe extract. The results showed total flavonoid, phenolic, and tannin levels were 7.41 ± 0.38 mg QE/mg, 1672 ± 50.99 mg GAE/g, and 1.43 ± 0.15 mg TAE/g, respectively. Scurrula ferruginea leaf ethanolic extract showed the potential to form an inhibition zone against S. aureus in the moderate category at 525 mg/mL, but no significant activity was observed against E. coli. The MIC results of Scurrula ferruginea leaf ethanolic extract against S. aureus were 0.6%, and the MBC was at 2.4%. Furthermore, the MIC value against E. coli was 14%, and the MBC value was 28%. Based on these results, it could be concluded that Scurrula ferruginea leaf ethanolic extract showed high effectiveness in inhibiting and killing S. aureus bacteria compared to E. coli, with MIC and MBC values of 0.6% and 2.4%, respectively Grand Forest Park (Tahura) Ir. H. Djuanda, Bandung, West Java, Indonesia is a secondary nature conservation area rich in biodiversity, including macrofungi which has not been widely studied. The research aims to isolate, characterize its morphology and screen its potential as a biomaterial source based on the growth of macrofungal mycelium. The research was carried out using an exploration method at three sampling locations: Maribaya (trail area), Goa Jepang (cave area), and Curug Koleang (waterfall area). The obtained macrofungi were isolated and identified based on their macroscopic and microscopic morphological characteristics and coded based on the location and number of isolates. A comparative evaluation was carried out by one-way Analysis of variance (ANOVA) to assess the average mycelial growth of the macrofungal isolates for 9 days on PDA. The results showed that there was a total of 62 species of macrofungi from three locations: 22 isolates from the Maribaya (MB) area, 18 isolates from the Goa Jepang (GJP) area, and 22 isolates from the Curug Koleang (CK) area. The isolates that showed the highest mycelium length and represented each research area were shown by MB-07 (63.98 ± 1.21 mm), GJP-01 (81.47 ± 0.41 mm) and CK-13 (72.14 ± 1.20 mm). Isolate GJP-01 from the Goa Jepang area has the potential to become a superior fungus in its ability to expand mycelium should be developed for mycelium-based material applications. Stevia rebaudiana Bert. (Stevia) is used in the commercial and health industries because of its steviol glycosides (stevioside, rebaudioside A, rebaudioside C) and flavonoids. Polyploidy induction of stevia plants using oryzalin was held to increase the diversity and produce superior varieties. This research aims to obtain stevia diversity with different characteristics from its diploid. The Tawangmangu variety of stevia seedlings was experimentally designed using a completely random design. Nine combinations of oryzalin concentrations (1.5, 2.5, and 3.5μM) and immersion times (4, 6, and 8 hours) treatments were applied to 15 stevia seedlings each. Stevia without treatment was used as a control. Treatments were applied directly to the shoots on the second internode from the tip. Observations on target shoots included the number of survivors, morphological variables (height, number of internodes, internode length, leaf size, leaf thickness, stem diameter, and leaf color), stomata, and plant ploidy level. Data analysis on the number of live plants used frequency and descriptively. Morphological data consisting of plant height, number of shoots, number of internodes, internode length, leaf length, leaf width, leaf thickness, and stem diameter were analyzed using boxplot graphs and descriptive to describe the diversity of M1 stevia treatment results. Leaf color and stomata were analyzed descriptively. The results showed that up to 3.5μM concentrations of oryzalin and 6 hours of immersion time were safe to use as a mutation agent with above 67% survival rate. Various oryzalin treatments of Tawangmangu stevia varieties yielded polyploidy morphological growth indications in height, number of internodes, internode length, stem diameter, leaf size, leaf thickness, leaf color, stomata, and stem diameter. In addition, there are growth variations such as chimeras, rosettes, and leaf splitting. However, further flow cytometry tests showed that oryzalin concentration and immersion duration directly on the vegetative material did not produce polyploid stevia individuals.